Analisis Terhadap RUU PRT Dalam Menjamin Kesejahteraan PRT Prespektif Undang Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan - Nurpradana, Resky Handagi (Media Hukum Indonesia (MHI), 2025)
Domestic Workers (PRT) play an important role in supporting domestic life and the Indonesian economy, but until now have not received proper legal protection. The Domestic Worker Protection Bill (RUU PRT) is present as a response to the imbalance in regulations that do not include PRT in Law Number 13 of 2003 concerning Manpower. In fact, the number of PRT in Indonesia is very significant and their contribution to maintaining the stability of urban households cannot be ignored. This study u physical ses a normative legal approach with a legislative and conceptual approach method. The results of the study show that the absence of a special legal umbrella makes PRT vulnerable to exploitation and discrimination, such as irregular working hours, inadequate wages, and verbal and violence. Therefore, the presence of explicit and biased regulations is very urgent. The urgency of ratifying the PRT Bill is very high to realize social justice and equal protection for all workers, including those working in the domestic sector.